Peruvian International Relations covered by Perú21 Newspaper. News Framing in Journalistic Information about Foreign Affairs - Gonzales García, Carlos Ricardo (2016)
This article aims to analyze the journalistic content of the newspaper Perú21, on the focus of interest information on international relations to know the frames or episodic and thematic frames in the news, and the approach saved with the official agenda of foreign affairs. The corpus consisted of 1295 journalistic texts produced between the months of July 2011 to July 2015. The different framings were determined on the basis of the theory of framing and typology of frames proposed by Semetko and Valkenburg. The results indicate that the news production issues Chancellery is defined primarily by the “attribution of responsibility” and “economic consequences”, particularly on issues of free trade and market economy, security and defense, human rights, fight against drug trafficking, the environment and technical cooperation.